Pendidikan dan Kebudayaan sebagai Pilar Penguatan Identitas Lokal di Lingkungan SMA - Ardhita, Fahra Putri; Mulyasaroh, Mulyasaroh; Nulhakim, Lukman (LPPM Institut Pendidikan Nusantara Global, 2025)
Education and culture play a central role in shaping the local identity of the younger generation, particularly at the secondary education level. In the context of globalization, which brings shifts in cultural values, schools must serve as strategic spaces to reintroduce local wisdom as part of strengthening students’ self-identity. According to research by Sari (2021), 75% of students involved in local culture-based learning programs reported an increased understanding of their region’s traditions and history. In addition, extracurricular activities that incorporate local arts and culture also contribute to identity reinforcement. This study aims to critically analyze the role of education and culture in strengthening local identity within the environment of upper secondary education. The method used is a literature review by examining various academic sources such as journals, books, policy documents, and previous relevant research. The analysis shows that integrating local cultural values into the curriculum and learning process can enhance cultural awareness, strengthen students’ connection to their social environment, and promote context-based character development. Culturally based education has been shown to contribute to the sustainability of local culture amid the pressures of global homogenization. Therefore, synergy among educational institutions, local communities, and policymakers is essential in mainstreaming local culture as the foundation of learning. The implications of this study provide a conceptual basis for developing educational strategies that are responsive to the social and cultural contexts of each region.